ORIENTASI KEPEMIMPINAN KIAI DAN PENDIDIKAN PESANTREN DI ERA MODERNISASI - Amini, Izzat; Ramadhan, Yusfar (Universitas Al-Amien Prenduan, 2021)
As a place of transmission of Islamic knowledge, pesantren are affected by the globalization. There are at least two attitudes taken by pesantren in the face of globalization; reject the principle of globalization, and accommodate and selectively for the essence of globalization while maintaining the principles of Islamic values. They are many steps must be taken immediately through by pesantren: improving the quality of the Kiai's leadership orientation and the orientation of the quality of Islamic boarding school education in the face of globalization. This research is a library research. The purpose of this study was to determine the leadership orientation of the kiai in the era of globalization and how the idealization of the orientation of pesantren education in the globalization. The results of this study is: First, Kiai's leadership orientation is based on: (1) orientation to produce the thought (2) orientation to creating relationships, and (3) orientation to the formation of work quality. Second, the orientation of pesantren education is based on: First, increasing institutional orientation through improving the quality of education and learning. Second, increasing the competence of the pesantren community and the life skills of graduates.